The Influence of Ballroom Dancing on the Development of Team Interaction Skills - Velykholova, Bohdan (European Journal of Interdisciplinary Issues, 2025)
The paper establishes that ballroom dancing is a powerful tool for developing team interaction skills, which are key to the successful implementation of joint dance programs. It was found that effective team interaction in ballroom dancing is based on multi-level coordination of partners' actions, which includes both strategic planning of the training process and direct performance of choreographic compositions. The results of the study revealed that the key factor in team interaction is communication, which is carried out in both verbal and non-verbal forms, however, in the process of direct dance, verbal signals are practically absent. It was found that non-verbal communication through dynamic impulses, facial expressions and tactile perception becomes the main means of supporting mutual understanding between partners. It was found that communicative interaction during the organization of the training process contributes to the development of mutual responsibility and involvement of partners in joint training. The results of the study showed that the awareness of the common goal of partners significantly increases motivation and reduces the level of conflict. It was found that openness to alternative points of view and consideration of the individual characteristics of partners contribute to the development of trust, empathy and reduction of psychological stress. It was found that constructive dialogue and active listening are necessary conditions for maintaining a high level of interaction and achieving high sports results. It was found that partnership work in this context functions as a multi-component system of interpersonal coordination, which ensures the effective implementation of complex choreographic tasks in a dynamic competition environment. It was determined that a special role in the formation and development of team skills is played by the formation format, which represents group dance interaction with the participation of 6–8 couples, who perform a choreographic composition to specially selected musical accompaniment in synchronous mode. The results of the study revealed that the formation acts as a unique model of collective motor activity, emphasizing the integrative nature of teamwork, where each couple functions as a structural unit of a larger system, which requires the organic integration of individual skills into a common motor pattern.